Fishmeal substitutions and their implications for aquatic animal immune and gut function: A review - Venerability Dhar; Soibam Khogen Singh; Swapnil Ananda Narsale; Sourabh Debbarma; Pritisha Saikia; Yilbong Yirang (Comparative Immunology Reports)
Fishmeal has long been a major ingredient in the aqua feed industry. However, as the aquaculture sector continues to grow rapidly, its heavy reliance on fishmeal is constrained by resource limitations and sustainability goals. Consequently, research has increasingly focused on alternative protein sources for feed preparation. This shift has gained momentum and success through the identification of suitable alternatives that do not compromise the growth of fish and shellfish. While alternative proteins can replace fishmeal to varying degrees, their effects are species-specific and dose-dependent. Unfortunately, many alternatives lack proper micronutrient composition and may contain toxic elements that could harm animal welfare. Plant-based proteins may change the gut flora and induce modest intestinal inflammation, but they may also moderately boost immune responses. Antioxidant capability and disease resistance can be enhanced by microbial and animal-based protein sources. The limited research reported on aquatic animals remains fragmented and requires systematic evaluation to focus on the immune and gut impairments caused by such substitutions. This review examines the impact of fishmeal replacement with alternative protein sources on the immunological function and gut health of aquatic animals in aquaculture. It synthesizes research on plant-based, animal-based, and microbial protein substitutes, evaluating their effects on the host microbiome, immune capacity, disease resistance, and intestinal histo-morphology. Finally, it stresses the need for species-specific and ingredient-specific evaluations to optimize aqua feeds and identifies knowledge gaps in long-term effects and underlying mechanisms.